The Influence of Work Environment and Competence on Employee Performance Through Work Discipline at the Public Works and Spatial Planning Office of Jambi City - Akbar, M. Adika Resindo; Zahari, M.; Akbar, Ali (Green Publisher, 2025)
This study aims to describe the work environment, competence, work discipline, and employee performance at the Public Works and Spatial Planning Office of Jambi City. It also seeks to determine the direct and indirect effects of the work environment and competence on employee performance, both directly and indirectly through work discipline. The population in this study consists of employees at departement of public works and spatial planning Jambi City, totaling 217 individuals. The sample size for this study was determined using Slovin's formula with a 10% margin of error, resulting in a sample of 69 respondents. This research employs a quantitative approach using survey methods and data analysis through Partial Least Squares (PLS). The results indicate that the work environment and competence have a positive and significant direct and indirect effect on employee performance through work discipline. Similarly, work discipline has a positive and significant direct effect on employee performance. These findings explain that a good and conducive work environment, supported by high employee competence—including relevant skills and knowledge—enables employees to perform their tasks more effectively. This directly impacts their discipline and performance in carrying out their duties.